2022
DOI: 10.1111/jocd.15078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a hyaluronic acid‐based mesotherapeutic injectable on the gene expression of CLOCK and Klotho proteins, and environmentally induced oxidative stress in human skin cells

Abstract: Objective Normal circadian rhythms are essential to the repair mechanisms of oxidative stress implicated in skin aging. Given reports that hyaluronic acid (HA) homeostasis exhibits a different profile in chronological skin aging, as compared to environmental or extrinsic aging, an improved understanding of the way HA interacts with its surroundings, and the impact of HA injectables in replacing lost HA and encouraging rejuvenation, is of key benefit to skin aging treatments. The objectives of these current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Skin photoaging is a complicated process in which skin changes are caused by persistent ultraviolet (UV) exposure [1][2][3]. Epidemiological studies and surveys have shown that skin photoaging contributes to the development of numerous skin disorders and skin tumors [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Skin photoaging is a complicated process in which skin changes are caused by persistent ultraviolet (UV) exposure [1][2][3]. Epidemiological studies and surveys have shown that skin photoaging contributes to the development of numerous skin disorders and skin tumors [4,5].…”
Section: Introductionmentioning
confidence: 99%